2012
DOI: 10.1590/s1677-55382012000400015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the deposition of collagen fibers and Lithogenic potential in bladder of rats submitted to a sugar cane biopolymer graft

Abstract: ARTIcLE INFO _________________________________________________________ ___________________Objectives: Suture materials are widely used in urology. The interaction of these materials with the extracellular matrix in the inflammatory process can be estimated by stereology of collagen fibers and the present study was designed to determine the behavior of the bladder tissue of rats to grafts of the biopolymer of sugar cane (BPCA), and the inflammation and intravesical stone formation compared to the polyglactin 91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
2
1
0
Order By: Relevance
“…Probably, this was the reason of SCB biodegradation in one SCB-6 group animal. This fact coincides with Carvalho Júnior's study [17]. Also there was no trace of SCB thread in one animal.…”
Section: Discussionsupporting
confidence: 91%
“…Probably, this was the reason of SCB biodegradation in one SCB-6 group animal. This fact coincides with Carvalho Júnior's study [17]. Also there was no trace of SCB thread in one animal.…”
Section: Discussionsupporting
confidence: 91%
“…BC hydrogel subcutaneous implants were found beneath the hypodermis layer of the skin, a slight inflammatory response was present and the formation of new vessels (neovascularization) was present in the majority of the animals. These effects are supported by previous studies (Rangel et al, 2006;Carvalho Junior et al, 2012;Cordeiro-Barbosa et al, 2012;Lima et al, 2015;Pita et al, 2015;Lima et al, 2017;Cavalcante et al, 2018;Gonçalves-Pimentel et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…In experimental studies the application of sugarcane biopolymer has shown adequate response in reconstruction of tympanic membrane (Mayer et al, 2011), fold vocal (Vasconcelos et al, 2015), osteochondral defect (Albuquerque et al), patch vascular (Marques et al, 2007), eviscerated eyes (Cordeiro-Barbosa et al, 2012) and bladder graft (Carvalho Junior et al, 2012). However, there are not records in scientific literature on the use this biopolymer in the treatment of nerve injuries.…”
Section: Introductionmentioning
confidence: 99%